Methodological proposal to evaluate public urban green spaces - Vidal, Diogo Guedes (2019)
Cities must be pleasant and healthy spaces able to contribute to ecosystems regeneration and to bring closer Humans and Nature. However, cities are unequal spaces regarding the distribution of environmental resources, resulting in environmental injustice: socioeconomic vulnerable areas are, simultaneously, those where is identified the bigger environmental vulnerability, in part due to the poor quality of public green spaces - resulting in poor air quality and the increase of noise level – and the social segregation. Therefore, the present work aim to present a methodological proposal to evaluate urban green spaces quality.